2001
DOI: 10.1038/89327
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive transgenic plant system to detect toxic inorganic compounds in the environment

Abstract: We describe a transgenic plant-based assay to study the genetic effects of heavy metals. Arabidopsis thaliana plants carrying a beta-glucuronidase (GUS) marker gene either with a point mutation or as a recombination substrate were used to analyze the frequency of somatic point mutations and homologous recombination in whole plants. Transgenic test plants sown on media contaminated by the salts of the heavy metals Cd2+, Pb2+, Ni2+, Zn2+, Cu2+, and As2O3 exhibited a pronounced uptake-dependent increase in the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 30 publications
1
48
1
1
Order By: Relevance
“…Similarly, in contrast with Molinier et al (2005) and Yao et al (2011), who found a seven-or threefold increase in recombination frequency, respectively, as a result of UV-C irradiation in Arabidopsis, Van der Auwera et al (2008) did not find a significant effect of UV-C in their SHR lines containing GUS recombination reporter (Van der Auwera et al, 2008). Furthermore, in contrast with earlier results (Kovalchuk et al, 2001b;Boyko et al, 2005), Van der Auwera et al (2008) reported that the presence of heavy metals, such as lead or cadmium ions, a heat shock of 50˚C, or growth at elevated temperatures and increased daylength had no measurable effect on the mutation or recombination frequencies . In contrast with the reported 1.5-fold to sevenfold increased recombination level in two tested Arabidopsis lines as a reaction to spraying plants with the salicylic acid analogs INA and benzothiadiazole (Lucht et al, 2002), or the results of Yao et al (2011) who used methyl salicylate, Van der Auwera et al (2008) did not find a significant difference when they added sodium salicylate to the growth medium (Van der Auwera et al, 2008).…”
Section: Conflicting Results From Shr Reporter Linescontrasting
confidence: 55%
See 1 more Smart Citation
“…Similarly, in contrast with Molinier et al (2005) and Yao et al (2011), who found a seven-or threefold increase in recombination frequency, respectively, as a result of UV-C irradiation in Arabidopsis, Van der Auwera et al (2008) did not find a significant effect of UV-C in their SHR lines containing GUS recombination reporter (Van der Auwera et al, 2008). Furthermore, in contrast with earlier results (Kovalchuk et al, 2001b;Boyko et al, 2005), Van der Auwera et al (2008) reported that the presence of heavy metals, such as lead or cadmium ions, a heat shock of 50˚C, or growth at elevated temperatures and increased daylength had no measurable effect on the mutation or recombination frequencies . In contrast with the reported 1.5-fold to sevenfold increased recombination level in two tested Arabidopsis lines as a reaction to spraying plants with the salicylic acid analogs INA and benzothiadiazole (Lucht et al, 2002), or the results of Yao et al (2011) who used methyl salicylate, Van der Auwera et al (2008) did not find a significant difference when they added sodium salicylate to the growth medium (Van der Auwera et al, 2008).…”
Section: Conflicting Results From Shr Reporter Linescontrasting
confidence: 55%
“…Analysis of several independent reporter lines carrying these marker genes indicated that the average somatic recombination frequency detected with the LUC transgene was ;10-fold higher (10 25 ) in Arabidopsis thaliana and tobacco (Nicotiana tabacum) plants compared with GUS recombination frequencies (Ilnytskyy et al, 2004). Using such GUS-or LUC-based SHR reporter lines, it was shown that abiotic and especially biotic stresses lead to enhanced somatic recombination (Kovalchuk et al, 1998(Kovalchuk et al, , 2001a(Kovalchuk et al, , 2001b(Kovalchuk et al, , 2003Lucht et al, 2002;Filkowski et al, 2004;Ilnytskyy et al, 2004;Molinier et al, 2004Molinier et al, , 2005Molinier et al, , 2006Schuermann et al, 2005). Using such a system, it was also discovered that plants can remember a stress perceived in one generation for several following generations.…”
Section: Somatic Homologous Recombination Reporter Lines: Lack Of Sufmentioning
confidence: 99%
“…These can be exploited as bioindicators of environmental pollution (Kovalchuk et al, 1998(Kovalchuk et al, , 2001a(Kovalchuk et al, , 2001b or as monitors of mutation frequencies resulting from mutant backgrounds or stress conditions in a laboratory setting (Lebel et al, 1993;Puchta et al, 1995;Kovalchuk et al, 2000Kovalchuk et al, , 2001bKovalchuk et al, , 2003Lucht et al, 2002;Leonard et al, 2003;Hoffman et al, 2004;Yoshihara et al, 2006). They provide either a direct or indirect way to determine the number of certain types of genome alterations.…”
mentioning
confidence: 99%
“…
Heavy metals are highly toxic for living organisms when excess amounts exist in the environment (Salt et al 1998;Kovalchuk et al 2001). Soils and water contaminated with heavy metals cause major environmental and human health problems.
…”
mentioning
confidence: 99%
“…During the last few decades, phytoremediation and plant-based assays for cleanup and monitoring of these contaminated environments have been developed (Salt et al 1998;Kovalchuk et al 2001;Krizek et al 2003;Pilon-Smits 2005). These methods take advantage of the sedentary nature of plants, providing inexpensive and nontechnical means of environmental analysis and restoration (Kovalchuk et al 2001;Krizek et al 2003).Among heavy metals, selenium and chromium function as toxic analogs of sulfur, and they exist in nature mainly as selenate (SeO 4 …”
mentioning
confidence: 99%